Formulation and in vitro Evaluation of Acemetacin Nanosuspension - Hussein Al-Gharani; Khalid Al-Kinani (Iraqi Journal of Pharmaceutical Sciences, 2025)
Acemetacin (ACM) is classified as a non-steroidal anti-inflammatory drug (NSAID). It is an indomethacin glycolic ester that is transformed into indomethacin in vivo. The analgesic, antipyretic, and anti-inflammatory properties of the ACM are attributed to its prostaglandin inhibitory action. Acemetacin belongs to biopharmaceutical classification system (BCS) class II drugs, which are characterized by having high permeability but poor aqueous solubility. The purpose of this study was to develop acemetacin nanoparticles (ACM NPs) for enhanced solubility and rate of dissolution. The solvent-anti-solvent approach was used to formulate the nanoparticles. Two stabilizers were used to prepare ACM NPs (sodium deoxycholate (SDC) and Soluplus®). Design Expert® software was used to create the experiments utilizing a computer-based approach. The Box-Behnken design was used for this purpose in order to investigate the effect of different formulation variables on particle size and polydispersity index (PDI) of ACM NPs. Using Soluplus® as a stabilizer, the chosen formula F22 has desirability value 0.701, and its particle size and PDI values were 59.69 nm and 0.1847 respectively. The saturated solubility of ACM in the generated nanoparticles was approximately ten times greater than that of the naked drug (25.01 μg/ml vs. 2.43 μg/ml), and a 100% dissolution was accomplished in 90 minutes compared to the naked ACM, which only gave 47% in this time frame. In conclusion, this is the first time reporting the preparation of ACM nanosuspension, and turning ACM into polymeric nanoparticles is an effective method to increase the solubility and rate of dissolution of the drug, readying it for incorporation into a dosage form requiring such properties.